Human and Technology Interaction: Consumer Perception Toward the Touch Screen Ordering Kiosk in Fast Food Restaurant - Yi Wen, Tian; Pakir Mohamed, Mohamed Ismail (Research in Management of Technology and Business, 2022)
The adoption of kiosks is getting common, but some uncertainty has not been discovered. The purpose of this research is to determine factors that influence the consumers’ perception of the features of touch screen ordering kiosks and identify the most critical element among the consumers’ perception of features of touch screen ordering kiosks. The factors that influence consumer perception encompass perceived usefulness, perceived ease of use, perceived enjoyment, and perceived risk. It is used to measure the consumers’ perception factor toward the design of the interface, security system, and responsiveness. This study investigates the consumer’s inclination via online questionnaires with a total of 330 online survey questionnaires. However, only 323 respondents are accepted because it only requires the consumer who has used the touch screen ordering kiosk at McDonald’s Muar. The result of the study provides empirical evidence on key issues relevant to customers of McDonald's Muar. The finding indicates that perceived usefulness, perceived ease of use, perceived enjoyment, and perceived risk were at a moderate level and there has a significant influence on the consumer perception toward the feature of touch screen ordering kiosks. In conclusion, even though this research is only focused on McDonald Muar, its finding did provide a better understanding of the factors that concerned consumers regarding the touch screen ordering kiosk and can be used as a reference and indication for improvement of the features of McDonald’s touch screen ordering kiosk.